Implementasi Pembelajaran Kontekstual Pada Era New Normal Berbasis Pendidikan Tri Hita Karana di Desa Medewi Kecamatan Pekutatan Kabupaten Jembrana - I Made Arsa Wiguna; Ni Ketut Srie Kusuma Wardhani; Ni Wayan Sariani Binawati; I Ketut Tanu; I Made Redana (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
The program of community service activity carried out by the Master Dharma Acarya (Hindu Education) in Medewi Village, Jembrana is the application of three obligations in higher education or called tri dharma. This program is based on several reasons. First, the obligation of higher education institutions, including lecturers and students, as a knowledge practices. Second, education and society have a strong relationship and influence each other. Third, education should be culture-based and oriented, so that the values ​​that exist in society need to be strengthened. Fourth, this community service is also a mandate from Hindu literature, that jnana yadnya is the main yadnya. The theme of this service is the application of contextual learning in the new normal era based on Tri Hita Karana. Theoretically and practically, this service activity refers to the concept of community-oriented contextual learning which includes seven things, namely: (1) meaningfulness and usefulness; (2) Utilization of the environment in learning; (3) Integrated learning materials in daily life; (4) The problems raised in the learning are in accordance with the needs; (5) Emphasis on participatory learning; (6) Fostering cooperation; and (7) Fostering independence. The reinforcement is in understanding, interpreting and using Tri Hita Karana in life. Theoretically, service participants who are members of the community are able to interpret the Tri Hita Karana philosophy and relate it to their daily religious life. Practically, participants are equipped to take advantage of the potential that exists in the surrounding environment to support or improve the quality of their health and life through the practice of processing medicinal plants sourced from Hindu literature such as Lontar Usadha Taru Pramana and herbal medicine practitioners who are also members of this community service team.